THE INFLUENCE OF FINANCIAL INTERNAL AND EXTERNAL FACTORS ON FIRM VALUE THROUGH PROFITABILITY AS A MODERATING VARIABLE IN TECHNOLOGY SECTOR COMPANIES - Surya, Vincent Alain; Ariesa, Yeni; Christian, Christian; Darmasaputra, Albert; Felim, Nicholas (SULTANIST: Jurnal Manajemen dan Keuangan, 2023)
This study aims to examine whether the internal factor (cash flow) and external factor (leverage) affect firm value through profitability as a moderating variable in technology sector companies 2018-2021. The method used in this research was a deductive approach, quantitative types, and descriptive characteristics. The number of technology sector companies listed on the IDX is 27 companies which the amount of sample that is selected by using purposive sampling technique is 5 companies. The SmartPLS 3.0 application was used in this study to make it easier for researchers to analyze data. The conclusion obtained show that internal (cash flow) and external (leverage) factors do not affect firm value through profitability as a moderating variable. However, researchers can prove that external factor (leverage) can affect profitability which is evidenced by the p-values in the hypothesis test, namely 0,010<0,05 which indicates that external factor (leverage) have a significant effect on profitability.Keywords: Internal Factor (Cash Flow), External Factor (Leverage), Profitability, and Firm Value.